Consolidative high-dose chemotherapy after conventional-dose chemotherapy as first salvage treatment for male patients with metastatic germ cell tumours - Beausoleil, Michel (Canadian Medical Association, 2012)
INTRODUCTION: Some men with metastatic germ cell tumours that have progressed after response to initial cisplatin-based combination chemotherapy are cured with conventional dose first salvage chemotherapy (CDCT) – however, many are not. High-dose chemotherapy with autologous stem cell rescue (HDCT) may be of value in these patients. Prognosis has recently been better defined by International Prognostic Factor Study Group (IPFSG) prognostic factors. HDCT after response to CDCT has been offered at our institution over the past two decades. We retrospectively assessed the validity of the IPFSG prognostic factors in our patients and evaluated the value of HDCT. METHODS: We identified eligible men with metastatic germ cell tumour progressed after at least 3 cycles of cisplatin-based chemotherapy and treated with cisplatin-based CDCT alone or with carboplatin-based HDCT. We also collected their clinical data. Patients were classified into risk groups using IPFSG factors, and progression-free and overall survival factors were analyzed and compared in patients treated with CDCT alone and with HDCT. RESULTS: We identified 38 eligible first salvage patients who had received a median of 4 cycles (range, 1 to 7 cycles) of CDCT. Twenty patients received CDCT alone and 18 patients received CDCT plus HDCT. The overall median progression- free survival was 24.6 months (95%CI, 7.3 to 28.7 months) and overall median overall survival was 34.6 months (95%CI, 17.2 to 51.3 months). Distribution by IPFSG category and 2-year progression- free survival and 3-year overall survival rates within each risk category were very similar to the IPFSG results. There were two toxic deaths with CDCT and none with HDCT. Overall, patients treated with CDCT plus HDCT had improved progression- free survival and overall survival. CONCLUSIONS: The IPFSG prognostic risk factors appeared valid in our patient population. The safety of HDCT with etoposide and carboplatin was confirmed. HDCT was associated with improved progression- free survival and overall survival outcomes, consistent with observations of the IPFSG group. Ideally, the value of optimal HDCT should be determined in comparison to optimal CDCT as first salvage therapy in men with metastatic germ cell tumour with a randomized trial.